Dynamics of Anisotropic Bianchi Type-III Bulk Viscous String Model with Magnetic Field - Singh M.K.; Ram S. (My University, 2025)
In this paper, we discuss the dynamics of spatially homogeneous and anisotropic Bianchi type-III string cosmological model in presence of bulk viscous fluid and electromagnetic field. Exact solutions of Einstein’s field equations are obtained by assuming (i) a special form of the deceleration parameter and (ii) the component $\sigma^{1}_{1}$ of the shear scalar tensor is proportional to mean Hubble parameter. The source of magnetic field is due to an electric current produced along z-axis. The role of bulk viscosity and magnetic field in establishing string phase of universe is presented. The physical and kinematical features of solutions are also discussed in detail. © 2014, Springer Science+Business Media New York.